2002
DOI: 10.1074/jbc.m108166200
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Phosphatidylinositol 3-Kinase, Rho Family GTPases, and STAT3 in Ros-induced Cell Transformation

Abstract: Using loss-of-function mutants of Ros and inducible epidermal growth factor receptor-Ros chimeras we investigated the role of various signaling pathways in Rosinduced cell transformation. Inhibition of the mitogenactivated protein kinase (MAPK) pathway with the MEK (MAP/extracellular signal-regulated kinase kinase) inhibitor PD98059 had little effect on the Ros-induced monolayer and anchorage-independent growth of chicken embryo fibroblasts and NIH3T3 cells even though more than 70% of the MAPK was inhibited. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 48 publications
5
32
0
Order By: Relevance
“…Overexpression of HMGA1 increases levels of Akt phosphorylation and Akt kinase activity PI3-K/Akt-signalling pathway is of critical importance in mediating anoikis resistance and enhancing anchorage-independent cell cycle progression (Moore et al, 1998;Nguyen et al, 2002). Given these observations, we sought to determine if HMGA1 overexpression would modulate Akt phosphorylation at Ser473, a marker of Akt activation.…”
Section: Hmga1 Overexpression Results In Protection From Caspasemediamentioning
confidence: 99%
“…Overexpression of HMGA1 increases levels of Akt phosphorylation and Akt kinase activity PI3-K/Akt-signalling pathway is of critical importance in mediating anoikis resistance and enhancing anchorage-independent cell cycle progression (Moore et al, 1998;Nguyen et al, 2002). Given these observations, we sought to determine if HMGA1 overexpression would modulate Akt phosphorylation at Ser473, a marker of Akt activation.…”
Section: Hmga1 Overexpression Results In Protection From Caspasemediamentioning
confidence: 99%
“…Akt activation through the expression of oncogenic Ras (29), or ectopic expression of constitutively active Akt (55), is sufficient to prevent anoikis. Others have reported that inhibitors of PI3K-Akt signaling, but not of the Ras-ERK pathway, inhibit anchorage-independent growth of fibroblasts induced by the v-Ros and epidermal growth factor receptor-Ros oncogenes (47). Interestingly, in a recent report, a genome-wide screen for suppressors of anoikis identified the TrkB (NTRK2) neurotrophin receptor as a key molecule in this process (19).…”
Section: Discussionmentioning
confidence: 99%
“…The serine/threonine kinase AKT, acting downstream of PI3K signaling, is a key regulator of multiple survival routes (32)(33)(34)(35)(36)(37). Previous studies focused on the effects of orexin-A on the MAPK pathway (6,25).…”
Section: Discussionmentioning
confidence: 99%